Lean Six Sigma approach to reduce LOS through a diagnostic-therapeutic-assistance path at A.O.R.N. A. Cardarelli. Issue 5 (10th October 2019) - Ricciardi, Carlo; Fiorillo, Antonella; Valente, Antonio Saverio; Borrelli, Anna; Verdoliva, Ciro; Triassi, Maria; Improta, Giovanni
Abstract : Purpose: The rise of the mean age incremented the occurrence of femur fractures with respect to the past, leading thus to serious consequences, as regards morbidity and socio-economic impact. The direction of the A.O.R.N. Cardarelli of Naples has introduced a DTAP whose aim was the reduction of LOS. The paper aims to discuss this issue. Design/methodology/approach: The aim of this paper is to analyze the introduction of DTAP, employing Lean Thinking and Six Sigma methodology based on the DMAIC cycle. To evaluate the effectiveness of DTAP, two groups of patients have been observed for 14 months (before and after the implementation of DTAP). Findings: Statistical tests were performed on the groups and graphics were provided to visualize the decrease of LOS (29.9 per cent). The overall population was also divided in subgroups according to six variables potentially influencing LOS. Research limitations/implications: Authors considered six variables of influences; yet, others could be taken into account in the future. Practical implications: The decrease of costs due to the management of elderly patients with femur fracture, the optimization of care processes in hospitals and a faster recovery for patients is the tangible contribute of DTAP. Originality/value: The implementation of DTAP allowed the hospital to obtain a significant reduction of LOS with a consequently decrease of costs alleviating the hospital and the society from the socio-economic burden and the morbidity of this pathology.